Focal cortical thickness correlates of exceptional memory training in Vedic priests - Kalamangalam, Giridhar P.; Ellmore, Timothy M. (Frontiers in Human Neuroscience, 2014)
The capacity for semantic memory – the ability to acquire and store knowledge of the world - is highly developed in the human brain. In particular, semantic memory assimilated through an auditory route may be a uniquely human capacity. One method of obtaining neurobiological insight into auditory semantic memory mechanisms is through the study of experts. In this work, we study a group of Hindu Vedic priests, whose religious training requires the memorization of vast tracts of scriptural texts through an oral tradition, recalled spontaneously during a lifetime of subsequent spiritual practice. We demonstrate focal increases of cortical thickness in the dominant prefrontal lobe and non-dominant temporal lobe in Vedic priests, in comparison to a group of matched controls. The findings are relevant to current hypotheses regarding cognitive processes underlying storage and recall of long-term declarative memory.